RAS protein activator like 2 promotes the proliferation and migration of pulmonary artery smooth muscle cell through AKT/mammalian target of Rapamycin complex 1 pathway in pulmonary hypertension. Issue 2 (1st February 2022) - Hu, Sheng; Zhao, Youguang; Qiu, Chenming; Li, Ying
ABSTRACT: RAS protein activator like 2 (Rasal2) exerts pro-proliferative effect in several types of cells. However, whether Rasal2 is involved in the regulation of pulmonary artery smooth muscle cell (PASMC) remains unclear. In the current study, we explored the role of Rasal2 in proliferation and migration of PASMC during the development of pulmonary arterial hypertension (PAH). We found that the protein level of Rasal2 was increased in both pulmonary arteries of chronic hypoxia-induced pulmonary hypertension (CH-PH) mice and hypoxia-challenged PASMC. Overexpression of Rasal2 caused enhanced proliferation and migration of PASMC after hypoxia exposure. Mechanistically, we found elevated phosphorylation of AKT and two downstream effectors of mammalian target of Rapamycin complex 1 (mTORC1), S6 and 4E-Binding Protein 1 (4EBP1) after Rasal2 overexpression in hypoxia-challenged PASMC. Inactivation of mTORC1 abolished Rasal2-mediated enhancement of proliferation and migration of PASMC. Furthermore, we also demonstrated that AKT might act downstream of Rasal2 to enhance the activity of mTORC1. Once AKT was inactivated by MK-2206 application, overexpression of Rasal2 failed to further increase the phosphorylation level of S6 and 4EBP1. Finally, inhibition of AKT also blocked Rasal2-induced proliferation and migration in hypoxia-challenged PASMC. In conclusion, Rasal2 promotes the proliferation and migration of PASMC during the development of PAH via AKT/mTORC1 pathway.